Cost‐effective development of highly polymorphic microsatellite in Japanese quail facilitated by next‐generation sequencing. (6th October 2014) - Tadano, R.; Nunome, M.; Mizutani, M.; Kawahara‐Miki, R.; Fujiwara, A.; Takahashi, S.; Kawashima, T.; Nirasawa, K.; Ono, T.; Kono, T.; Matsuda, Y.
Summary Next‐generation sequencing technologies permit rapid and cost‐effective identification of numerous putative microsatellite loci. Here, from the genome sequences of Japanese quail, we developed microsatellite markers containing dinucleotide repeats and employed these for characterisation of genetic diversity and population structure. A total of 385 individuals from 12 experimental and one wild‐derived Japanese quail lines were genotyped with newly developed autosomal markers. The maximum number of alleles, expected heterozygosity and polymorphic information content (PIC) per locus were 10, 0.80 and 0.77 respectively. Approximately half of the markers were highly informative (PIC ≥ 0.50). The mean number of alleles per locus and observed heterozygosity within a line were in the range of 1.3–4.1 and 0.11–0.53 respectively. Compared with the wild‐derived line, genetic diversity levels were low in the experimental lines. Genetic differentiation (FST) between all pairs of the lines ranged from 0.13 to 0.83. Genetic clustering analyses based on multilocus genotypes of individuals showed that most individuals formed clearly defined clusters corresponding to the origins of the lines. These results suggest that Japanese quail experimental lines are highly structured. Microsatellite markers developed in this study may be effective for future genetic studies of Japanese quail.